A monodispersed CuPt alloy: synthesis and its superior catalytic performance in the hydrogen evolution reaction over a full pH range. Issue 21 (29th March 2021) - Liu, Xinmei; Liang, Chen; Yang, Wenlong; Yang, Chunyang; Lin, Jiaqi; Li, Xue
Abstract : An effective approach to achieve the low cost and high stability of electro-catalysts for HER. Abstract : The high cost and low stability of electrocatalysts are the major challenges for the commercialization of hydrogen generation in water. In this study, we demonstrated a one-pot synthesis of a monodispersed CuPt alloy with the diameter range of 20–30 nm by a hydrothermal method. Benefiting from the more available active sites and preferable d-band structure, the CuPt alloy exhibited a superior catalytic performance than pure Pt nanoparticles (Pt NPs) in the hydrogen evolution reaction (HER). In acidic media, the CuPt alloy achieved a low overpotential of 39 mV at a current density of 10 mA cm −2 for HER, which was by 22 mV lower than that for pure Pt NPs. In a neutral solution, the stability of the CuPt alloy is ca. 100-fold as compared to pure Pt NPs. Accounting by the dissolution of Cu in the alloy phase, the performance of the CuPt alloy was elevated after yielding hydrogen for 1.2 × 10 5 s in alkaline media. The superior catalytic activity can also be applied in other applications. In the reduction of 4-nitro-phenol (4-NP), the CuPt alloy showed 12.84-fold catalytic activity higher than pure Pt NPs. This study designed a low-cost electrocatalyst with an efficient and durable catalytic performance for HER over the full pH range, which provides an environmentally friendly strategy to cope with the challenges of hydrogen generation.